Health Workers’ Experiences and Challenges in Providing Comprehensive Antenatal Care in Rural Primary Health Centers in West Nias District - Putri Ayu Yessy Ariescha; Peny Ariani; Nur Mala Sari; Friska Ernita Sitorus (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Antenatal care (ANC) plays a critical role in reducing maternal and neonatal risks, yet its delivery in rural and remote areas remains constrained by geographic isolation, limited health resources, workforce shortages, and sociocultural barriers. This study explored the experiences and challenges of health workers in providing comprehensive ANC services in rural primary health centers in West Nias District, North Sumatra, Indonesia. A qualitative study with a grounded theory approach was conducted among 16 health workers, consisting of 11 midwives and five physicians, who were selected through purposive sampling. Data were collected through in-depth semi-structured interviews, supported by field notes, limited participant observation, and review of relevant service documents. Data were analyzed using open, axial, and selective coding. The findings identified professional resilience as the core category explaining how health workers sustain ANC services in resource-limited and culturally complex settings. This resilience was shaped by four interrelated themes: limited resources and infrastructure, human resource constraints, sociocultural influences, and adaptation strategies. Health workers maintained service continuity through manual examination methods, mobile services, home visits, informal counseling, community-based education, and collaboration with village leaders, religious leaders, and traditional birth attendants. These strategies helped strengthen community trust and improve access to ANC services. The study highlights the need to strengthen rural maternal health systems through improved infrastructure, adequate staffing, supportive supervision, and culturally responsive service planning Keywords: Antenatal Care, Health Workers, Maternal Health, Professional Resilience, Rural Health Services, Community Collaboration